2015
DOI: 10.1111/pan.12609
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of the i‐gel with the self‐pressurized air‐Q intubating laryngeal airway in children

Abstract: Our results showed that the i-gel had easier insertion and better sealing function, and the air-Q SP provided improved fiberoptic views in children requiring general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
61
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 24 publications
6
61
1
1
Order By: Relevance
“…The oropharyngeal leak pressure is consistent with previous studies reporting 21 to 26 cm H 2 O. [1214] In comparison, gastric insufflation was presented in 20.6% of patients in our study, which is higher than in a study by Kim et al (9%) [13] but lower than observed in another study by Kim et al (30%). [14] This discrepancy might be related to the detection period.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The oropharyngeal leak pressure is consistent with previous studies reporting 21 to 26 cm H 2 O. [1214] In comparison, gastric insufflation was presented in 20.6% of patients in our study, which is higher than in a study by Kim et al (9%) [13] but lower than observed in another study by Kim et al (30%). [14] This discrepancy might be related to the detection period.…”
Section: Discussionsupporting
confidence: 92%
“…Gastric insufflation was detected on US in 3 of that 8 cases. In most studies, including our study, [13,14,20] ventilation was acceptable in grade 3/4, but increased PIP following grade worsening may induce gastric insufflation and oropharyngeal leakage during PPV. [4,6] If there is no room for the escape of air outside the oral cavity, leaked oropharyngeal gas can be forced into the stomach.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Hier besteht der den larynxumschließende Anteil aus einem thermoplastischen Elastomer, das durch Körperwärme weicher wird und sich somit der jeweiligen Anatomie anpasst. Diese findet auch bei Kindern zunehmend Einsatz[19,24,33], Studien zur i-gel® sind im Folgenden aber noch nicht berücksichtigt. Ein aus der klinischen Praxis häufig berichtetes Problem scheint die spontane Dislokationstendenz zu sein, die in weiteren Kinderstudien noch evaluiert werden muss.Abgewinkelte, gebogene LM mit vorgeformter L-Form (z.…”
unclassified